Pembuatan Alat Ukur Multi Kanal Kelembaban Tanah Berbasis Mikrokontroler Arduino Uno - Mila Kharisma; Iwan Sugriwan; Ade Agung Harnawan (Lambung Mangkurat University Press, 2019)
Soil moisture very important to be measured per unit of time, especially in peat soils that have high porosity value. The measuring device for detection of soil moisture is realized on this research. The soil moisture measuring instrument is built by three main blocks of an instrument, that are four soil moisture sensors YL-69s, Arduino Uno as measurement processing unit that equipped with sd card as data storage unit and 20x4 character LCD as a display unit of the measurement result. The span value of the measuring device ranges from 0% to 95 % with deviation from 0% to 4.88%.The advantages of the measurement instrument system are simple in the operational process, real-time monitoring and stored automatically.